ANALISIS PENGUASAAN KATA KOMPLEMEN â€œGUOLAIâ€, â€œGUOQUâ€, â€œCHULAIâ€, â€œCHUQUâ€ PADA MAHASISWA ANGKATAN 2017 UNIVERSITAS TANJUNGPURA - Jumana, Jumana; Ina, Ina; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The words complement the direction of the compound is one form of sentencewhich is often used in mandarin chinese and is an important material in theteaching of mandarin. For exsample, the word complement the direction of thecompound ?guolai?, ?guoqu?, ?chulai?, ?chuqu? which is often used ineveryday life. In terms of its meaning, the fourt of these words have similaritiesand differences, so that students are often wrong in laying the fourth word in thesentence. To understand the condition of mastery of the students of the chineselanguage study frogram of FKIP Tanjungpura University against the said?guolai?, ?guoqu?, ?chulai?, ?chuqu? the authors use the testing method toexsamine the understanding and difficulties of students to the word ?guolai?,?guoqu?, ?chulai?, ?chuqu?. From the results of the study, the authorsconcluded that the percentage of complement the direction of the compound?guolai?, ?guoqu?, ?chulai?, ?chuqu? on the student force 2017 is 68,93%,55,80%, 57,59%, 64,73%. In the analysis of the types of difficulties, the authors found a mistake that often happens is the fault of the selection of said.Keywords: Mastery Analysis Guolai, Guoqu, Chulai, Chuqu Complement